Analysis of Volatile Component Profile of Bekasam Seluang Fish (Rasbora argyrotaenia - Herni Noormaliani; Yuspihana Fitrial; Agustiana (Universitas Islam Lamongan, 2025)
Seluang fish is a freshwater fish commonly found in Southeast Asian waters, including Indonesia. Fermentation, autolytic and enzymatic degradation of protein and fat produce volatile compounds such as organic acids, carbonyls, nitrogen compounds, and sulfur. The research aims to analyze the identification of volatile compounds in bekasam seluang fish. The research was conducted at the Integrated Laboratory, Lambung Mangkurat University, Banjarbaru, using a four-treatment design and three replications, namely: O (without roasted rice), A (50% roasted rice), B (60% roasted rice), and C (70% roasted rice). Analysis of volatile components was carried out using Gas Chromatography-Mass Spectrometry (GC-MS), an instrumental technique for separating and identifying compounds in complex samples. Volatile components using GC-MS Headspace revealed that the addition of roasted rice affected the complexity of the volatile compounds formed. The higher the concentration of roasted rice, the more volatile compounds typical of fermentation were formed, such as pyrazine, methanol, methyl uronate, and isoleucinol. The 60% roasted rice treatment produced the most complex but balanced volatile compound profile, while 70% produced compounds with a strong aroma but potentially masked the characteristic aroma of fish.